Creep behavior of a nickel-based superalloy under cyclic temperatures. (15th March 2021) - Zhang, Qiang; Hu, Xiaoan; Li, Bin; Yang, Xiaoguang; Jiang, Yun; Sun, Yantao; Zhang, Shengliang
Abstract: In this paper, the thermal-cycling creep of Ni-based superalloy DZ125 is investigated at very high temperature. Experiments were conducted with various parameters including overheating duration, applied stress, temperature interval and heating/cooling frequency. Microscopic observation has revealed a modified thermodynamic equilibrium with lower γ' content in comparison to isothermal creep situation. This phenomenon is discussed on the basis of Johnson-Mehl-Avrami-Kolmogorov law and pre-existing theoretical assumptions of dislocation density evolution during thermal transients. A linear relationship between overheating numbers and equilibrium γ' content is obtained to develop a phenomenological life model of thermal-cycling creep. Life prediction results of proposed method are in good agreement with experimental ones. Graphical abstract: In this work, the decrease of γ' content at thermodynamic equilibrium of Ni-based superalloys during thermal-cycling creep(TCC) process is quantitatively analyzed to obtain a microstructure-based failure criterion. A modification on JMAK law is proposed to illustrate why the γ' content at thermodynamic equilibrium differs with the length of overheating duration. A creep life prediction method is developed to evaluate TCC lives based on proposed failure criterion. The predicted results are well consistent to the experimental results. Image, graphical abstract